Factors impacting participation of European elite deaf athletes in sport - Kurková, P.; Válková, H.; Scheetz, N. (Journal of Sports Sciences, 2011)
This study examine 53 European elite deaf athletes for their family's hearing status, use of hearing aids, communication preference, education in integrated or segregated settings, family members' encouragement for participation in sports, coach preference (hearing or deaf), and conditions for competitive events with deaf or hearing athletes. These data were gathered through semi-structured interviews administered in the athlete's native language. Deaf athletes reported that when given the opportunity to compete with hearing athletes, it enhanced their opportunity for competition. Participating in sports with hearing athletes played an important role in the integration of deaf athletes into mainstream society. If adaptations to communication can be made in these integrated settings, the ability of deaf athletes to participate in such settings will increase.